2019
DOI: 10.32479/irmm.7976
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Financial Dimensions of Lebanese Smes: Comparative Study Between Family and Non-Family Business

Abstract: This study investigates the financial dimensions of family and non-family SMEs in Lebanon from 2005 to 2016. Based on 81 family SMEs and 45 non-family SMEs, the results reveal that family SMEs have outperform the non-family SMEs during economical and political instability period. In addition, the results show that family SMEs rely on long term debts (LTD) more than non-family SMEs. Oppositely to non-family SMEs, when the level of risk increased with local and regional instability in the period between 2005 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
(65 reference statements)
0
11
0
2
Order By: Relevance
“…This has also been discovered when Tuan et al ’s (2016) study found positive impacts by process, marketing and organizational innovations on firm performance. Other studies have also established that innovative capabilities do significantly impact a firm’s performance (El Chaarani and El Abiad, 2019; Afriyie et al , 2019; Hsieh and Lin, 2010). This is also reaffirmed by Cai and Li (2018), who said that, when different types of innovations, such as eco-innovation, are adopted, it can ominously boost a firm’s performance, and indirectly impact its financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This has also been discovered when Tuan et al ’s (2016) study found positive impacts by process, marketing and organizational innovations on firm performance. Other studies have also established that innovative capabilities do significantly impact a firm’s performance (El Chaarani and El Abiad, 2019; Afriyie et al , 2019; Hsieh and Lin, 2010). This is also reaffirmed by Cai and Li (2018), who said that, when different types of innovations, such as eco-innovation, are adopted, it can ominously boost a firm’s performance, and indirectly impact its financial performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, other studies of the same nature, namely Adusei (2015), Caprio and Klingebiel (2002) and Demirgüç-Kunt and Huizinga (1999), supported the importance of bank profitability in predicting financial distress and bank crisis. In other words, the investigation into the profitability determinants among commercial banks is called for, in terms of the banks' competitiveness, overall stability and efficiency (Adelopo et al, 2018;Al-Harbi, 2019;C apraru & Ihnatov, 2015;Dietrich & Wanzenried, 2014;El-Chaarani, 2019;Menicucci & Paolucci, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the financial crisis that broke out in 2007-2008 brought researchers towards directing their focus to the issue (Al-Harbi, 2019;Bourke, 1989;Menicucci & Paolucci, 2016;Short, 1979). Thus, the consequential global financial crisis and its outcome among the global system worldwide highlight the significance of maintaining the stability of banking system (Al-Harbi, 2019;Batten & Xuun Vinh, 2017;Batten & Vo, 2019;El-Chaarani, 2019;Menicucci & Paolucci, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lebanon’s local and international NGOs play a fundamental role in the provision of services, delivering welfare, technical, legal and financial services to the huge poor community. Lebanon is suffering from economic recession, government corruption and political crises since 2010, and thus has led to an increase in the level of poverty (El-Chaarani and El-Abiad, 2017; El-Chaarani and El-Abiad, 2019). The development role of NGOs in Lebanon extends to precipitating social change and policy reforms through direct lobbying and social advocacy.…”
Section: Literature Reviewmentioning
confidence: 99%